Preliminary study of coach verbal behaviour according to game actions - Guzmán, J. F.; Calpe-Gómez, V. (Journal of Human Sport & Exercise, 2012)
The aim of this study was to analyse the interaction between game actions in high-level handball and verbal behaviour performed by the coach. For this purpose, a match of the 1st National Division of male Spanish handball was analysed. The type of behaviour and the content of the message reported by the coach were recorded using a modified version of Coaching Behaviour Assessment System (CBAS) and Coach Analysis and Intervention System (CAIS). About game actions, they were grouped into positive and negative. Statistically significant differences were obtained in both the coach`s type of behaviour (Chi-square = 63.978, df = 13, Sig <0.001) and message content (Chi-square = 19.401, df = 6, Sig = 0.004) according the game action performed previously (positive or negative). After positive actions coach performed more positive feedback and encouragement, and after negative actions coach performed more negative feedback and queries, and content of communication was more related with results of technical-tactical action. Results offer some clues about specific coach behaviours that may be game action dependent. This knowledge may be useful to implement interventions to improve coaches` behaviour. However, more in depth studies with bigger samples are necessary.